Go Ahead, Please!—Evaluation of External Human—Machine Interfaces in a Real-World Crossing Scenario - Loew, Alexandra; Graefe, Julia; Heil, Lukas; Guthardt, Anne; Boos, Annika; Dietrich, André; Bengler, Klaus (Frontiers in Computer Science, 2022)
In the future, automated vehicles without human drivers will potentially have to manage the communication with vulnerable road users, such as pedestrians, in daily traffic interaction situations. This work aims to investigate pedestrian reactions to external communication concepts in a controlled, but real-world crossing scenario. The focus was to investigate which properties of external human-machine interfaces (eHMIs) promote the comprehension of the vehicle’s intent (yielding for the pedestrian) and therefore lead to faster, and at the same time safer, crossing decisions of pedestrians. For this purpose, three different eHMI concepts (intention-based light-band, perception-based light-band, combination of light-band and signal lamp) were examined and compared to a baseline (no eHMI). In a Wizard-of-Oz experiment, the participants (N = 30) encountered a test vehicle equipped with the eHMIs in a real-world crossing scenario. The crossing initiation time in seconds and the intention recognition of the participant were measured. Furthermore, it was evaluated how acceptance and perceived safety were influenced by the eHMIs. It was shown that the presence of the intention-based light-band, and the combination of light-band and signal lamp led to an earlier crossing decision compared to the baseline without an eHMI. In summary, the results indicate that the intention-based light-band has a positive effect on the comprehensibility of the vehicle's intention. All concepts were positively evaluated regarding acceptance and perceived safety, they did not differ significantly from each other.